Comparison of mineralogical, mechanical and hygroscopic characteristic of earthen, gypsum and cement-based plasters - Santos, Tânia (2022)
This study was supported by Operational Programme Competitiveness and Internationalization (COMPETE 2020), by FEDER funds through the Regional Operational Programs of Lisbon and of Center (Lisbon 2020, Center 2020) and by national funds through the Portuguese Foundation for Science and Technology (FCT) in the scope of the project SAICT/23349/2016: INDEEd -Indoor air quality regulation through the usage of eco-efficient mortars and project PTDC/EPH-PAT/4684/2014: DB-HERITAGE - Database of building materials with historical and heritage interest. Acknowledgments are due to Aldeias de Pedra, Embarro, Secil Argamassas and Sival Companies for providing the materials and pre-mixed mortars.